Creative Thinking-Oriented Students' Scientific Literacy Skills: Preliminary Study - Coryna Oktaviani; Seprianto Seprianto; Mentari Darma Putri (Postgraduate, University of Mataram, 2023)
This research is a descriptive quantitative that aims to determine the understanding of science teachers and students' knowledge in solving creative thinking-oriented scientific literacy questions. The instruments used in this research were a teacher interview questionnaire and creative thinking-oriented scientific literacy essay questions. Teacher interview data were analyzed using a descriptive percentage, and student test results were analyzed using descriptive statistics by calculating the average percentage score for creative thinking-oriented scientific literacy skills based on scientific literacy indicators and creative thinking indicators. The results of the analysis show that 83.33% of teachers still rarely and almost never use scientific literacy and creative thinking assessments in science learning. Meanwhile, in the results of the analysis of the students' test data, the average percentage for the scientific literacy indicator was 22.86% and the creative thinking indicator was 23.23% with the predicate of very poor and in the low category. Thus, it can be concluded that the understanding of junior high school science teachers in Langsa City in developing creative thinking-oriented scientific literacy assessments is still low. This has an impact on the students' abilities, which show that the creative thinking-oriented scientific literacy skills are classified as very poor in the low category